1998
DOI: 10.1007/s007010050166
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Metabolites Activate the Sphingomyelin Pathway and Induce Death of Glioblastoma Cells

Abstract: 1 alpha, 25-dihydroxyvitamin D3 was previously shown to induce cell death in brain tumour cell lines when added to the medium at micromolar concentration. In this paper we show that Cholecalciferol, a poor ligand of the vitamin D receptor, also induces cell death of HU197 human glioblastoma cell line and early passages cultures derived from a recurrent human glioblastoma. This finding suggests that the effects of vitamin D metabolites on brain tumour cells are at least partially independent from the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…UVB irradiance varies inversely with latitude [27] , and photosynthesis in the skin resulting from it is the source of approximately 95% of circulating vitamin D and its metabolites in humans [28] . Previous studies have shown that 25(OH)D [14] and its precursor, vitamin D 3 [15] , can inhibit growth or destroy human glioblastoma cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UVB irradiance varies inversely with latitude [27] , and photosynthesis in the skin resulting from it is the source of approximately 95% of circulating vitamin D and its metabolites in humans [28] . Previous studies have shown that 25(OH)D [14] and its precursor, vitamin D 3 [15] , can inhibit growth or destroy human glioblastoma cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…These adhesion proteins can be degraded by ionizing radiation, the principal known risk factor for brain cancer. In addition, vitamin D 3 (cholecalciferol) has been shown to induce death of human glioblastoma cells in vitro [14] and another study found that 25(OH)D can cause a significant reduction in growth of glioblastoma cells in vitro [15] .…”
Section: Introductionmentioning
confidence: 99%
“…1a,25-dihydroxyvitamin D 3 (1a,25(OH) 2 D 3 or calcitriol), the hormonally active form of vitamin D is not only a regulator of calcium and phosphate homeostasis but also an effective modulator of cellular proliferation and differentiation in a number of different cell types, including breast, colon and prostate cancer as well as melanoma, myeloma and gliablastoma cells (James et al, 1996;Magrassi et al, 1998;Blutt et al, 2000), for a review see Tuohimaa et al, 2001;Ylikomi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When evaluated in vitro studies planned to explain the relationship between vitamin D and GBM, generally their results shown vitamin D and its metabolites induce death of GBM cell lines (Naveilhan et al, 1994;Baudet et al, 1996;Magrassi et al, 1998). One of the effects of sunlight exposure on cancer prognosis may be mediated by vitamin D and its metabolites.…”
Section: Discussionmentioning
confidence: 99%